Induced After-Death Communication (IADC) Therapy: An Effective and Quick Intervention to Cope with Grief - D’Antoni, Fabio; Pulvirenti, Irene; D’Orlando, Antonella; Claudio, Vilma; Lalla, Claudio (Psychology International, 2025)
Background: Induced after-death communication (IADC) therapy is an emerging approach for addressing grief-related distress, particularly in individuals experiencing complicated grief (CG). Developed from eye movement desensitization and reprocessing (EMDR), IADC therapy aims to change the meanings with which loss is read and to transform acute grief into integrated grief. While spontaneous after-death communications (ADCs) have been widely reported across different cultures, IADC therapy provides a structured procedure for inducing a state of mind in which such experiences can spontaneously arise and develop. Methods: This study employed a prospective observational cohort design with a retrospective analysis, comparing the effectiveness of IADC therapy (experimental group, n = 42) to standard grief interventions combining talk therapy and EMDR (control group, n = 43). Participants completed standardized measures, including the Inventory of Complicated Grief (ICG) and the IADC Grief Questionnaire (IADC-GQ), at pre-treatment (T1), post-treatment (T2), and six-month follow-up (T3). Additional analyses explored the role of spirituality, religious affiliation, and therapist characteristics in grief processing. Results: IADC therapy led to a significantly greater reduction in grief intensity (ICG scores) immediately after the intervention and at the six-month follow-up compared to the control group. The experimental group also showed a more pronounced decrease in distress symptoms (CS scores) and higher ratings of therapeutic satisfaction. Furthermore, participants in the experimental group exhibited a significantly greater increase in their continuing bond (CB) scores, suggesting a more adaptive connection with the deceased. Additional analyses examined therapist characteristics, treatment-related factors, and the nature of ADC experiences, which are further explored in the discussion. Conclusions: These findings highlight the clinical utility of IADC therapy as a brief and cost-effective grief intervention, offering comparable or superior outcomes to traditional grief therapies. The results suggest that recognizing and integrating spontaneous ADC experiences into grief therapy may provide a valuable therapeutic pathway. Future research should further explore the long-term effects, cultural variations, and therapist characteristics to optimize the integration of IADC therapy into mainstream clinical practice.